Abnormal peritoneal regulation of chemokine activation—The role of IL‐8 in pathogenesis of endometriosis. (25th January 2017) - Sikora, Justyna; Smycz‐Kubańska, Marta; Mielczarek‐Palacz, Aleksandra; Kondera‐Anasz, Zdzisława
Abstract : Problem: Endometriosis is a chronic inflammatory disease associated with an impairment in immune response. Disorders in the peritoneal fluid and ectopic endometrium macrophage populations and their secretory products create a specific microenvironment inducing the development of the disease. The important factors involved in inflammation associated with endometriosis are chemokines, especially interleukin (IL)‐8. For this reason, the current study briefly reviews the role of IL‐8 in the pathogenesis of endometriosis. Method of study: A systematic review was done on all published studies that compared IL‐8 expression and concentration in patients with and without endometriosis to evaluate their potential as biomarkers for the disease. Results: IL‐8 induces chemotaxis of neutrophils and other immune cells; also, it is a potent angiogenic agent. Most researchers pointed to the increased peritoneal and serum IL‐8 levels and showed correlation with the severity of the disease, size and number of the active lesions. IL‐8 takes part in all processes during the development of the disease: adhesion, invasion, and implantation of ectopic tissue. Additionally, the chemokine plays a role in growth and maintenance of ectopic endometrial tissue directly affecting endometrial cell proliferation. IL‐8 might also protect ectopic cells against death by apoptosis. Conclusion: It may act as an autocrine growth factor in the endometrium and promotes the vicious circle of endometrial cell attachment and, in consequence, may lead to a transformation from acute to chronic inflammation stage.